2004
DOI: 10.1007/s00198-004-1739-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone density and hemoglobin levels in older persons: results from the InCHIANTI study

Abstract: Hypoxemia has been recognized as a risk factor for bone loss. The aim of the present study is to investigate the relationship of bone mass and density measures with anemia and hemoglobin levels in a large sample of older community-dwelling persons. The study is based on data from 950 participants enrolled in the ''Invecchiare in Chianti'' (Aging in the Chianti area, InCHIANTI) study. All the analyses were performed considering continuous hemoglobin levels as well as the dichotomous anemia variable (defined acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 43 publications
5
63
2
Order By: Relevance
“…[10][11][12][13][14] The current study reported an adverse economic association between CKD and all-cause health care costs in…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…[10][11][12][13][14] The current study reported an adverse economic association between CKD and all-cause health care costs in…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…Our study had several strengths, including a large sample size, sound sampling method, and stricter selection criteria for patients diagnosed with IDA or osteoporosis. One advantage of our study was that the sample was retrieved from the database of a general survey involving a national population rather than purposive sampling or special age (elderly) or gender (female) groups [17][18][19]. The sample size of the current study was large among all studies of its kind to investigate the incidence of osteoporosis for patients with anemia.…”
Section: Discussionmentioning
confidence: 99%
“…All biases resulting from the samples, the selection, the investigator, and the measuring process were minimized by the methods and criteria used. Additionally, we analyzed the effects of blood transfusion and intravenous ferrum therapy used for correcting anemia on subsequent osteoporosis, which has not been previously reported [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations